Comprehensive Evaluation and Future Perspectives of Non-Surgical Contraceptive Methods in Female Cats and Dogs - Sheila I. Peña-Corona; Melissa Aurea Vaquera-Guerrero; José Cerbón-Gutiérrez; Juan I. Chávez-Corona; Adrián E. Iglesias-Reyes; Alonso Sierra-Reséndiz; Juan José Pérez-Rivero; Socorro Retana-Márquez; Pablo Adrián Vizcaino-Dorado; David Quintanar-Guerrero; Gerardo Leyva-Gómez; Dinorah Vargas-Estrada (Animals)
The issue of stray cats and dogs is a global concern with considerable implications for animal welfare and public health. This review aims to provide an updated and comprehensive analysis of non-surgical contraceptive methods tested in studies controlled in vivo in feline and canine females. Immunocontraception via vaccination against gonadotropin-releasing hormone (GnRH), the luteinizing hormone receptor, zona pellucida proteins, and sperm, or use of viral-vectored delivery, is yet developing. Hormonal treatment (progestins, androgens, or GnRH) analogs act directly to block the reproductive axis. However, it produced essential side effects. Analogs of kisspeptin, non-steroid anti-inflammatory drugs such as firocoxib, and delivery of cytotoxins to the pituitary have shown non-conclusive results. Additional methods have also been tested, such as intraovarian injection of necrosing compounds or intravaginal and intrauterine devices. At present, neither of these methods offers permanent sterility that can replace surgical sterilization techniques. To our knowledge, none are currently authorized by the Food and Drug Administration (FDA) or the European Medicines Agency (EMA) for contraceptive methods or sterilization of cats or dogs. Therefore, it is necessary to continue the development of a compound that warrants the sterility of cats and dogs.